Meso-Foundations of Experiential Education in Ontario Universities: A Content Analysis of the Province’s Strategic Mandate Agreements - LaCroix, Emerson (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2024)
Experiential education, the process of providing students with applied learning opportunities within and outside the classroom, is rife with organizational complexity. This article examines Ontario’s Strategic Mandate Agreements using qualitative content analysis to see how conceptions and communications of experiential learning have changed over time, and how universities have responded to government pressure to foster experiential learning. Drawing on frame analysis, findings reveal that universities have developed a considerable amount of institutional infrastructure and initiatives to support the expansion of experiential learning, and these efforts have been framed in relation to current discourse about graduate skill readiness. However, these outward signalling responses are not necessarily aligned with internal organizational processes (i.e., expansion of co-curricular learning). These mandate agreements represent official accounts of institutional priorities, which leave the door open for future research to examine micro-foundations of experiential learning through the perspectives of the faculty and staff inhabiting these institutions.